Complex Formation of Co(II) and Cu(II) Metal Ion Complexes with Substituted Isoxazolines - V. Tekade, Pradip; Patil, K.N.; Narwade, M.L.; Bodkhe, P.S.; Meshram, Y.K. (Asian Journal of Chemistry, 2010)
The interactions of Co(II) and Cu(II) with 3-(2´-hydroxy-4´-methyl-5´-chlorophenyl)-4-(2´- chlorobenzoyl-5-(4´-N,N-dimethyl aminophenyl) isoxazoline (Ligand I), 3-(2´-hydroxy-4´- methyl-5´-chlorophenyl)-4-(2´-chlorobenzoyl)-5-(4´-methoxy phenyl) isoxazoline (ligand II) and 3-(2´-hydroxy-4´-methyl-5´-chlorophenyl)-4-(2´-chlorobenzoyl)-5-phenyl isoxazoline (ligand III) have been studied by spectrophotometric technique at 0.1 M ionic strength and (30 ± 0.1ºC) in 70% dioxane-water mixture. The data obtained were used to estimate the values of metal-ligand stability constant of substituted isoxazoline. Spectrophotometric investigation of Co(II) and Cu(II) complexes with ligand (I), ligand (II) and ligand (III) showed 1 : 1 complex formation. The formation of complexes has been studied by Job's variation method. The results obtained of stability constants are in good agreement.